Don't go [large type] - Scottoline, Lisa (Thorndike Press, A part of Gale, Cengage Learning, 2013)
Fleeing home from his military service in Afghanistan when his wife dies in an apparent freak household accident, Dr. Mike Scanlon struggles with the tragedy, his inability to bond with his new baby daughter and a downsizing in his medical practice only to discover a shocking secret that changes his understanding of everything.